Influence of high-energy electrons irradiation on nanoceramics properties of zirconia - Aizatskyi, M.I.; Dikiy, N.P.; Dovbnya, A.N.; Fedorets, I.D.; Kushnir, V.A.; Lyashko, Yu.V.; Medvedev, D.V.; Mytrochenko, V.V.; Onishchenko, I.N.; Perezhogin, S.A.; Pelichatyi, N.M.; Danilenko, I.A.; et al. (Вопросы атомной науки и техники, 2013)
Radiation defects in nanoceramics zirconia were investigated after electron irradiation with energy 41…89 MeV up to doze 2.28…5.7·10¹⁴ electrons/cm². Radioactive isotopes ⁸⁷,⁸⁸Y, ⁸⁸,⁸⁹,⁹⁵Zr, ⁹⁵Nb, ¹⁷⁵Hf are registered after irradiation of electrons with energy 41 and 47.2 MeV. The activity of ⁸³Rb was registered after irradiation by electrons with energy 86 and 88.9 MeV. Activity of ⁸³Rb can be formed in reactions (γ, 6n) or (e, 6n). Different process of annealing radiation defects in samples of nanoceramics is detected after irradiated by electrons with energy 41…47.2 or 86…88.9 MeV. The colour centres for samples of nanoceramics after irradiated by electrons with energy 41…47.2 MeV practically completely was annealed at 500°С. For samples of nanoceramics after irradiated by electrons with energy 86…88.9 MeV and after annealing at 500°С significant absorption for lengths of waves of 430 and 470 nm is observed. It is supposed that these distinctions at annealing the colour centres of zirconia are caused by formation in nuclear reactions by high-energy electrons on isotopes of a matrix of krypton atoms. The krypton atoms are the centres segregation point defects. As a result the steady defective complexes were formed.